SIRT1 overexpression in the rheumatoid arthritis synovium contributes to proinflammatory cytokine production and apoptosis resistance. Issue 10 (8th July 2011) - Niederer, Fabienne; Ospelt, Caroline; Brentano, Fabia; Hottiger, Michael O; Gay, Renate E; Gay, Steffen; Detmar, Michael; Kyburz, Diego
Abstract : Objective: To analyse the expression of SIRT1 in synovial tissues and cells of patients with rheumatoid arthritis (RA) and to study the function of SIRT1 in inflammation and apoptosis in RA. Methods: Levels of SIRT1 expression were analysed in synovial tissues and cells from patients with RA by real-time PCR and western blotting before and after stimulation with toll-like receptor ligands, tumour necrosis factor α (TNFα) and interleukin 1β (IL-1β). Immunohistochemistry was used to study the localisation of SIRT1. Fluorescence activated cell sorting analysis was performed to investigate the effect of SIRT1 on apoptosis. Peripheral blood monocytes and rheumatoid arthritis synovial fibroblasts (RASFs) were transfected with wild-type or enzymatically inactive SIRT1 expression vectors or with siRNA targeting SIRT1. Cytokine analysis of IL-6, IL-8 and TNFα were performed by ELISA to study the role of SIRT1 on proinflammatory mediators of RA. Results: SIRT1 was found to be constitutively upregulated in synovial tissues and cells from patients with RA compared to osteoarthritis. TNFα stimulation of RASFs and monocytes resulted in further induced expression levels of SIRT1. Silencing of SIRT1 promoted apoptosis in RASFs, whereas SIRT1 overexpression protected cells from apoptosis. Inhibition of SIRT1 enzymatic activity by inhibitors, siRNA and overexpression of an enzymatically inactive form of SIRT1 reduced lipopolysaccharide-induced levels of TNFα in monocytes. Similarly, knockdown of SIRT1 resulted in a reduction of proinflammatory IL-6 and IL-8 in RASFs. Conclusion: The TNFα-induced overexpression of SIRT1 in RA synovial cells contributes to chronic inflammation by promoting proinflammatory cytokine production and inhibiting apoptosis.